Epimedin C enhances mitochondrial energy supply by regulating the interaction between MIC25 and UBC in rodent model - Mi Huang; Lei Yu; Zhong Li; Ying Wang; Chunlin Yang (PLoS ONE, 2025)
The study investigates the molecular mechanisms underlying the skeletal muscle-enhancing effects of Epimedin C, a natural flavonoid, focusing on its interaction with the mitochondrial cristae structural protein MIC25. Using C57BL/6 mice, we demonstrate that Epimedin C enhances exercise performance through preservation of mitochondrial function. Proteomic analysis identified MIC25 as a key protein modulated by Epimedin C, whose stability is regulated via ubiquitin-dependent degradation. Functional experiments revealed that Epimedin C disrupts the interaction between MIC25 and ubiquitin-conjugating enzyme C (UBC), preventing MIC25 degradation and maintaining the integrity of the mitochondrial contact site and cristae organizing system (MICOS). This stabilization preserves mitochondrial cristae structure, improves ATP production, and delays muscle fatigue. Notably, MIC25 overexpression mimicked Epimedin C’s effects, while its knockdown abolished these benefits. Our findings establish MIC25 as a critical effector of Epimedin C, elucidating a novel pathway through which flavonoids maintain mitochondrial homeostasis to enhance muscle function. These insights hold promise for developing therapies targeting muscle atrophy and metabolic disorders.